Floods types in a mountain catchment: The Ochotnica River, Poland - Kijowska-Strugała, Małgorzata; Bucała-Hrabia, Anna (Acta geographica Slovenica, 2019)
This paper presents the results of a study on floods in the Ochotnica River catchment during forty years of hydrological observations (1972–2011). The Ochotnica River is located in the Gorce Mountains, in the Polish Western Carpathians. The characteristics of floods in the Ochotnica River channel were analyzed using limnigraphic records of water levels at the Tylmanowa gauging station and of precipitation based on data from the Polish Institute of Meteorology and the Water Management Station at Ochotnica Górna. Flood types were determined. The predominant type of floods in the Ochotnica River are normal floods with a discharge of 3.80 to 11.94 m³/s in winter and 4.74 to 16.40 m³/s in summer. The dominant recent process is incision, at an average speed of 3.2 cm/year. Similar results have been observed in other mountain rivers in Europe.